A prospective analysis of the long-term impact of the COVID-19 pandemic on well-being and health care among children with a chronic condition and their families: a study protocol of the KICK-COVID study - Petra Warschburger; Clemens Kamrath; Stefanie Lanzinger; Claudia Sengler; Susanna Wiegand; Julia M. Göldel; Susann Weihrauch-Blüher; Reinhard W. Holl; Kirsten Minden (BMC, 2023)
Abstract Background There is consistent evidence that the COVID-19 pandemic is associated with an increased psychosocial burden on children and adolescents and their parents. Relatively little is known about its particular impact on high-risk groups with chronic physical health conditions (CCs). Therefore, the primary aim of the study is to analyze the multiple impacts on health care and psychosocial well-being on these children and adolescents and their parents. Methods We will implement a two-stage approach. In the first step, parents and their underage children from three German patient registries for diabetes, obesity, and rheumatic diseases, are invited to fill out short questionnaires including questions about corona-specific stressors, the health care situation, and psychosocial well-being. In the next step, a more comprehensive, in-depth online survey is carried out in a smaller subsample. Discussion The study will provide insights into the multiple longer-term stressors during the COVID-19 pandemic in families with a child with a CC. The simultaneous consideration of medical and psycho-social endpoints will help to gain a deeper understanding of the complex interactions affecting family functioning, psychological well-being, and health care delivery. Trial registration German Clinical Trials Register (DRKS), no. DRKS00027974. Registered on 27th of January 2022.